Ferrite powder, ferrite resin composite material, electromagnetic shielding material, electronic material or electronic parts

JP7630833B2Active Publication Date: 2025-02-18POWDERTECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021551690
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-07
Filing Date
2020-10-07
Publication Date
2025-02-18
Estimated Expiration
2040-10-07

AI Technical Summary

Benefits of technology

【0021】 本発明によれば、複合材料や複合体に適用したときに、成形性及び充填性を損なうことなくフェライト粒子の脱落を抑制できるフェライト粉末、フェライト樹脂複合材料並びに電磁波シールド材料、電子材料又は電子部品が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007630833000017
    Figure 0007630833000017
  • Figure 0007630833000018
    Figure 0007630833000018
  • Figure 0007630833000019
    Figure 0007630833000019
Patent Text Reader

Abstract

Provided are: a ferrite powder whereby, when the ferrite powder is applied in a composite material, dropping out of ferrite particles is suppressed without moldability and filling ability being compromised; a ferrite resin composite material; and an electromagnetic shielding material, an electronic material, or an electronic component. This ferrite powder includes at least spherical or polyhedral ferrite particles in which a step structure is provided on surfaces thereof, the step structure having a polyhedral outline in the surfaces of the ferrite particles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a ferrite powder, a ferrite-resin composite material, an electromagnetic shielding material, an electronic material, or an electronic part. [Background technology]

[0002] Composite materials made of ferrite powder and resin are widely used in various applications, including electromagnetic shielding materials. Such composite materials are produced by kneading ferrite powder with resin. The composite material is molded into a shape such as a sheet to form a composite (molded body). In this case, if the shape of the particles that make up the ferrite powder is close to spherical, the fluidity during molding is high and the filling rate of the ferrite powder in the composite is high. This results in good moldability and good properties such as electromagnetic shielding performance. From this perspective, ferrite powder (particles) made up of spherical or polyhedral particles have been proposed.

[0003] For example, Patent Document 1 (WO 2017 / 212997) discloses ferrite particles that are single crystals having an average particle size of 1 to 2000 nm and a spherical particle shape, the ferrite particles being substantially free of Zn and containing 3 to 25% by weight of Mn and 43 to 65% by weight of Fe, and characterized in that the real part of the complex permeability measured using a molded body made of the ferrite particles and a binder resin has a maximum value in the frequency band of 100 MHz to 1 GHz. It is described that when the ferrite particles are used as an electromagnetic wave shielding material for electronic devices, electromagnetic waves in a wide frequency band can be stably shielded regardless of frequency (Claim 1 and

[0078] of Patent Document 1).

[0004] Patent Document 2 (JP Patent Publication No. 2016-60682) discloses a spherical ferrite powder that contains 15 to 30 weight % ferrite particles with a particle size of less than 11 μm and has a volume average particle size of 10 to 50 μm. It describes that the powder has good filling and moldability when used as a filler, has excellent handleability, and has high resistance. Therefore, the spherical ferrite powder is combined with a resin to form a resin composition, and the resulting molded product can be used for various applications including an IC sealant for absorbing electromagnetic waves (Claim 1 and

[0093] of Patent Document 2).

[0005] Patent Document 3 (WO 2018 / 061327) discloses Ni-Zn-Cu ferrite particles that are single crystals having an average particle size of 1 to 2000 nm, have a polyhedral particle shape, and contain 5 to 10 weight % Ni, 15 to 30 weight % Zn, 1 to 5 weight % Cu, and 25 to 50 weight % Fe. It is described that the ferrite particles have both high saturation magnetization and high electrical resistance, and are therefore suitable as a magnetic filler or a raw material for compacts (Claim 1 and

[0089] of Patent Document 3).

[0006] Patent Document 4 (JP 2006-160560 A) discloses spherical sintered ferrite particles having (a) a soluble ion content of 5 ppm or less, (b) an average particle size in the range of 10 to 50 μm, and (c) a crystal structure determined by X-ray diffraction that exhibits a spinel structure. It also describes that a resin composition for semiconductor encapsulation that contains a filler consisting of the spherical sintered ferrite particles and silica particles has low viscosity and good flow characteristics, and also has electromagnetic wave shielding properties, and that by using this resin composition as an encapsulating material, the resulting semiconductor device has excellent EMC (Claim 1 and

[0023] of Patent Document 4).

[0007] Patent Document 5 (JP Patent Publication 04-304700A) discloses a powder for use in radio wave absorber materials, which is made of Mn-Zn ferrite particles, characterized in that the particles are spherical and have an average particle size of 50 to 150 μm. It describes that by making the average particle size 150 μm or less, clogging of the gate during injection molding, which has been an obstacle to increasing the particle size of the material, can be improved by improving fluidity (see claims 1 and

[0008] ).

[0008] In addition, although it is used for purposes other than composite materials such as electromagnetic wave shielding materials, Patent Document 6 (Patent Publication No. 5921801) describes Fe as a raw material. 2 O 3 Powder and this Fe 2 O 3 A method for producing a carrier core material for an electrophotographic developer is disclosed, which is characterized in that a mixture of a carbonate as an auxiliary raw material in an amount of 10 to 50 g per 10 kg of powder and a reducing agent is granulated and then fired at a temperature of 1000°C or less to produce a carrier core material having step-like irregularities, which are a collection of concentrically spreading raised parts on the surface of the particles, and it is stated that the carrier core material has a sphericity of 0.8 or more (claim 1 and

[0024] of Patent Document 6). [Prior art documents] [Patent documents]

[0009] [Patent Document 1] International Publication No. 2017 / 212997 [Patent Document 2] JP 2016-60682 A [Patent Document 3] International Publication No. 2018 / 061327 [Patent Document 4] JP 2006-160560 A [Patent Document 5] Japanese Patent Application Publication No. 04-304700 [Patent Document 6] Patent No. 5921801 Summary of the Invention [Problem to be solved by the invention]

[0010] In this way, it has been proposed to improve the moldability and filling property of composite materials and composite bodies by using spherical or polyhedral ferrite powder. However, the inventors have found that when a composite body is produced using such ferrite powder and a resin, there is a problem that the ferrite particles tend to fall off from the composite body. In particular, many ferrite particles were found to fall off (detached particles) during processing of the composite body. Such falling off of ferrite particles is undesirable because it leads to deterioration of the smoothness of the surface of the composite body.

[0011] In investigating the cause of particle shedding, the present inventors considered that spherical or polyhedral ferrite particles have poor adhesion to resin because their surfaces are too smooth. As a result of further investigation, they found that even if spherical or polyhedral ferrite particles are used, the adhesion to resin can be improved by providing a polygonal step structure on the surface, and that ferrite powder containing such particles can suppress particle shedding without impairing moldability and packing property when used in composite materials or composites, and thus completed the present invention.

[0012] Therefore, an object of the present invention is to provide a ferrite powder, a ferrite resin composite material, an electromagnetic shielding material, an electronic material, or an electronic component that can suppress particle shedding without impairing moldability and packing property when applied to a composite material or composite. [Means for solving the problem]

[0013] The present invention encompasses the following aspects (1) to (7). In this specification, the expression "to" includes both ends of the expression. In other words, "X to Y" is synonymous with "X or more and Y or less."

[0014] (1) At least spherical or polyhedral ferrite particles having a step structure on the surface, The step structure has a polygonal contour on the surface of the ferrite particle.

[0015] (2) The ferrite powder according to (1) above, wherein the step structure has two or more steps.

[0016] (3) The ferrite powder according to (1) or (2) above, wherein the ferrite powder has a shape factor SF-1 of 100 to 110.

[0017] (4) The ferrite powder according to any one of the above (1) to (3), wherein the ferrite powder has a 50% diameter (D50) in a volume particle size distribution of 0.10 to 20.00 μm.

[0018] (5) The ferrite powder according to any one of (1) to (4) above, wherein the ferrite powder has a manganese (Mn) ferrite composition having a manganese (Mn) content of 4.0 to 17.0 mass% and an iron (Fe) content of 50.0 to 70.0 mass%.

[0019] (6) A ferrite resin composite material comprising the ferrite powder according to any one of (1) to (5) above and a resin.

[0020] (7) An electromagnetic wave shielding material, electronic material, or electronic part, comprising the ferrite resin composite material of (6) above. Effect of the Invention

[0021] According to the present invention, there are provided a ferrite powder, a ferrite resin composite material, an electromagnetic shielding material, an electronic material, and an electronic component, which can suppress the falling off of ferrite particles without impairing moldability and packing property when applied to a composite material or a composite. [Brief description of the drawings]

[0022] [Figure 1] 1 shows a surface SEM image of an example sample. [Diagram 2] 1 shows a surface SEM image of an example sample. [Diagram 3]1 shows a schematic cross-sectional view of a step structure. [Figure 4] 1 shows a surface SEM image of a comparative sample. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] A specific embodiment of the present invention (hereinafter, referred to as the present embodiment) will be described. Note that the present invention is not limited to the following embodiment, and various modifications are possible within the scope of the present invention.

[0024] 1. Ferrite powder The ferrite powder of the present embodiment contains at least spherical or polyhedral ferrite particles having a step structure on the surface thereof. The step structure has a polygonal outline on the surface of the ferrite particle.

[0025] The ferrite powder of the present embodiment is composed of a plurality of ferrite particles. That is, the ferrite powder is an aggregate of a plurality of ferrite particles. The ferrite powder also contains at least spherical or polyhedral ferrite particles (spherical step particles) having a step structure on the surface. That is, the ferrite particles constituting the ferrite powder may be partly or entirely spherical step particles.

[0026] By making the particles contained in the ferrite powder spherical or polyhedral, the moldability and packing properties of the powder can be improved. This is because spherical or polyhedral particles can smoothly avoid contact with other particles during molding. This improves the flowability during molding and packs densely. In contrast, particles with anisotropic or irregular shapes such as plate-like or needle-like shapes are inferior in moldability and packing properties.

[0027] When ferrite powder contains components with high saturated vapor pressure, such as zinc (Zn) or strontium (Sr), the particles tend to become polyhedral. This is thought to be because during the high-temperature heating (spraying) process in the production of ferrite powder, the components with high saturated vapor pressure move from the inside of the particles to the outside and act as a flux, which makes it easier for the particles to grow into polyhedrons that reflect the crystal structure. On the other hand, when ferrite powder does not contain components with high saturated vapor pressure, for example, when it has a composition such as manganese (Mn) ferrite, the particles tend to become spherical.

[0028] Polyhedral particles basically have a shape in which a plurality of polygons are combined three-dimensionally. The polygons constituting the polyhedron are typically triangles, squares, hexagons, octagons, decagons, or combinations thereof. An example of such a polyhedron is a rhombic truncated cuboctahedron consisting of a square, a hexagon, and an octagon. The more faces a polyhedron has, the closer it is to a sphere. Therefore, the polyhedral particles preferably have a shape of 10 or more, more preferably 12 or more, and even more preferably 14 or more. The polyhedral particles typically have a shape of 100 or less, more typically 72 or less, and even more typically 24 or less.

[0029] In addition, particles in which one or more straight lines constituting a polygon are broken, or particles in which some straight lines are curved, are also included in the polyhedral particles, so long as they can be recognized as polyhedral when viewed as a whole particle. In addition, particles in which the straight lines constituting a polygon are finely jagged are also included in the polyhedral particles. Furthermore, spherical-like stepped particles have a step structure on their surface, and strictly speaking, they may not be completely spherical or polyhedral. However, this step structure is much smaller than the size of the particle. Therefore, particles that have such a microscopic step structure but have a spherical or polyhedral shape when viewed macroscopically are considered to be spherical or polyhedral particles.

[0030] The ferrite powder of this embodiment has a step structure in the ferrite particles (spherical step particles). This step structure will be described with reference to Figs. 1 and 2. Figs. 1 and 2 are surface SEM images of spherical step particles in one aspect of this embodiment. As can be seen from Figs. 1 and 2, the particle surface is not smooth, but a step structure is formed. By including particles having such a step structure, when the ferrite powder is applied to a composite material or composite, the adhesion with the resin is improved and particle dropout is suppressed. Although the detailed mechanism is unknown, it is speculated that the presence of the step structure on the particle surface increases the surface area of ​​the particle, that is, the contact area with the resin, and as a result, the chemical bonding force between the particle and the resin is increased. It is also speculated that the particle and the resin are fitted together at the steps of the step structure, which causes the anchor effect of the resin to work and increases the physical bonding force between the particle and the resin.

[0031] The step structure has a polygonal outline on the ferrite particle surface. That is, when the particle is viewed from the surface, the step structure has a polygonal outline. In other words, the step structure is provided so as to surround one area of ​​the particle surface with a combination of straight lines. By providing such a step structure, it is possible to more effectively prevent the particles from falling off. The outline of the step structure is not limited as long as it is polygonal. However, reflecting the crystal structure of ferrite, the outline is typically a triangle, a square, a hexagon, an octagon, or a decagon. The ferrite particle may also have a plurality of step structures on its surface. This makes it possible to more effectively prevent the particles from falling off. The number of step structures provided on each ferrite particle is preferably 4 to 50, more preferably 4 to 30.

[0032] The outline of the step structure is preferably endless, i.e., composed of a closed straight line shape. However, even if one or more of the straight lines constituting the outline are broken, if part of the straight line is curved, or if the straight line has fine jagged edges, the outline is still considered to be polygonal as long as it can be recognized as a polygon when viewed as a whole.

[0033] The step structure may be made up of one or more steps. However, the more steps there are, the more effectively the particles can be prevented from falling off. Therefore, the number of steps is preferably two or more, and more preferably four or more. On the other hand, if the number of steps is too large, the fluidity of the ferrite powder may deteriorate. Therefore, the number of steps is preferably 100 or less, and more preferably 80 or less. When the step structure is made up of multiple steps, the area surrounded by the steps in the upper stages is slightly smaller than the area surrounded by the steps in the lower stages. In other words, the step structure can be said to be made up of a stack of polygonal plates with smaller areas in the upper stages.

[0034] When the step structure is composed of multiple steps, the average interval (Hs) of the steps is preferably 0.001 to 0.2 μm (1 to 200 nm). Here, the average interval (Hs) is the average value of the distance between adjacent steps in the step structure. This will be explained using FIG. 3. FIG. 3 shows a schematic cross-sectional view of a multiple step structure. As shown in FIG. 3, a multiple step structure has multiple steps, and adjacent steps are separated by a certain distance. The average value of the distance between the adjacent steps is defined as the average interval (Hs) of the steps. The average interval (Hs) can be obtained by observing the surface of the ferrite particles using a scanning electron microscope (SEM) or the like. Hs is more preferably 3 nm or more, and more preferably 10 nm or more. Hs is more preferably 100 nm or less, more preferably 50 nm or less, and particularly preferably 25 nm or less.

[0035] When the volume average particle size (D50) is 2.00 μm or more, the content ratio (Ps) of spherical step particles in the ferrite powder is preferably 3% or more, more preferably 20% or more, and even more preferably 60% or more, based on the number of particles. The higher Ps is, the better the adhesion with the resin is and the more the particles are prevented from falling off. Therefore, the higher Ps is, the better. However, it is typically 90% or less, more typically 80% or less, and even more typically 70% or less. Ps can be determined by observing the ferrite powder with a scanning electron microscope (SEM) or the like. Ps can also be adjusted by controlling the conditions during the production of the ferrite powder.

[0036] On the other hand, when the volume average particle diameter (D50) is 0.10 μm or more and less than 2.00 μm, the content ratio (Ps) of spherical step particles in the ferrite powder is preferably 0.5% or more, more preferably 1% or more, and even more preferably 2% or more, based on the number of particles. The higher the Ps, the better the adhesion with the resin and the more the particles are prevented from falling off. However, it is the particles of 0.3 μm or more that cause a problem in terms of detachment from the resin. If the volume average particle diameter is within the range of 0.10 μm or more and less than 2.00 μm, the particle diameter is relatively small and the BET specific surface area is large. Therefore, it is sufficient that Ps is in the range of 0.5% or more. Ps is typically 60% or less, more typically 45% or less, and even more typically 30% or less. Ps can be obtained by observing the ferrite powder with a scanning electron microscope (SEM) or the like. Ps can also be adjusted by controlling the conditions during the production of the ferrite powder.

[0037] The ferrite powder preferably has a shape factor SF-1 of 100 to 110. SF-1 is an index of the sphericity of the particles constituting the powder, with a perfect sphere being 100, and increasing as the particles deviate from a sphere. By making SF-1 110 or less, the fluidity of the powder is increased, regardless of whether the particles are spherical or polyhedral, and the moldability and packability are improved. SF-1 is more preferably 105 or less, and even more preferably 103 or less.

[0038] The shape factor SF-2 of the ferrite powder is preferably 100 to 110. SF-2 is an index showing the degree of unevenness of the particle surface constituting the powder. If there is no surface unevenness, SF-2 is 100, and the deeper the unevenness, the higher it becomes. The ferrite powder of this embodiment has a microscopic step structure on the particle surface, which improves adhesion with resin when made into a composite material or composite, thereby suppressing particle dropout. Therefore, a moderately high SF-2 is preferable. SF-2 is more preferably 101% or more. On the other hand, if SF-2 is excessively high, the powder will have poor flowability, and there is a risk of deterioration in moldability and filling ability. SF-2 is more preferably 105 or less.

[0039] The ferrite powder preferably has a 50% diameter (volume average particle diameter; D50) in its volume particle size distribution of 0.10 to 20.00 μm. By making D50 0.10 μm or more, the aggregation of the ferrite powder can be suppressed, and the moldability and packing properties are more excellent. On the other hand, by making D50 20.00 μm or less, the generation of interparticle voids can be suppressed, and the packing properties are more excellent. D50 is more preferably 0.50 μm or more, even more preferably 0.60 μm or more, particularly preferably 0.80 μm or more, and most preferably 1.00 μm or more. Moreover, D50 is more preferably 10.00 μm or less, even more preferably 8.00 μm or less, particularly preferably 6.00 μm or less, and most preferably 4.00 μm or less.

[0040] In the ferrite powder, the content of particles of 0.3 μm or more in the particle size distribution measurement described later is preferably 0.1% by number or more, more preferably 5.0% by number or more, even more preferably 10.0% by number or more, and most preferably 20.0% by number or more. The number distribution is measured by converting the volumetric particle size distribution measurement result into number distribution data.

[0041] The tap density of the ferrite powder is 0.50 to 3.50 g / cm 3 It is preferable that the density is 1.00 to 3.00 g / cm 3It is more preferable that the tap density is increased by mixing small particles with large particles, and as a result, the packing property of the ferrite powder is improved overall.

[0042] The ferrite powder has a BET specific surface area of ​​0.35 to 10.00 m 2 / g. The BET specific surface area is preferably 10.00 m 2 By setting the specific surface area to 0.35 m / g or less, the aggregation of the ferrite powder can be suppressed, and the moldability and packing properties can be improved. 2 By making the BET specific surface area 0.50 m or more, it is possible to suppress the generation of voids between particles, resulting in better packing properties. In addition, by making the BET specific surface area within the above range, the adhesion to resins is improved when the ferrite powder is applied to composite materials or composites. The BET specific surface area is 0.50 m 2 / g or more is more preferable. The BET specific surface area is 7.50 m 2 / g or less is more preferable, and 5.00m 2 / g or less is more preferable, and 2.50m 2 / g or less is particularly preferred.

[0043] The composition of the ferrite powder is not particularly limited. However, it is preferable that the ferrite powder has a composition of manganese (Mn) ferrite. Manganese (Mn) ferrite is a ferrite that mainly contains manganese (Mn), iron (Fe), and oxygen (O), and may contain other components such as magnesium (Mg), zinc (Zn), and / or strontium (Sr). Manganese (Mn) ferrite may have a composition that does not contain other components, contains manganese (Mn), iron (Fe), and oxygen (O), and the balance is unavoidable impurities. The manganese (Mn) content of the ferrite powder is preferably 4.0 to 17.0 mass%, and the iron (Fe) content is preferably 50.0 to 70.0 mass%. By using such a composition, the magnetic properties of the ferrite powder and the composite material or composite produced using it can be improved. The manganese (Mn) content is more preferably 4.0 to 11.0 mass%, and further preferably 5.0 to 10.0 mass%. The iron (Fe) content is more preferably 60.0 to 65.0 mass %, and further preferably 61.0 to 65.0 mass %.

[0044] 2. Ferrite powder manufacturing method The ferrite powder of the present embodiment can be produced by any method, but can be produced by spraying a mixture of ferrite raw materials under predetermined conditions and then quenching the mixture, as described below.

[0045] <Raw material mixture> First, the ferrite raw materials are mixed to prepare a raw material mixture. As the ferrite raw materials, known ferrite raw materials such as oxides, carbonates, hydroxides and / or chlorides can be used. The raw materials can be mixed using a known mixer such as a Henschel mixer in either a dry or wet manner, or both.

[0046] <Pre-calcination and grinding> Next, the obtained raw material mixture is pre-calcined to obtain a pre-calcined product. The pre-calcination may be performed by a known method. For example, it may be performed using a furnace such as a rotary kiln, a continuous furnace, or a batch furnace. The pre-calcination conditions may also be known. For example, the pre-calcination conditions include maintaining the mixture at 700 to 1300°C for 2 to 12 hours in an atmosphere such as air.

[0047] <Granulation> The resulting calcined product is then pulverized and granulated to obtain a granulated product. The pulverization method is not particularly limited. For example, a known pulverizer such as a vibration mill, a ball mill, or a bead mill may be used, and either or both of a dry method and a wet method may be used. The granulation method may also be a known method. For example, water and, if necessary, additives such as a binder such as polyvinyl alcohol (PVA), a dispersant, and / or an antifoaming agent may be added to the calcined product after pulverization to adjust the viscosity, and then the product is granulated using a granulator such as a spray dryer.

[0048] In the production of ordinary ferrite particles, the binder component is removed before the main sintering. In contrast, in the present embodiment, it is preferable not to perform the binder removal process. By performing thermal spraying while the binder component is contained, it becomes possible to stably generate a step shape.

[0049] As mentioned above, when the manufactured ferrite powder contains components with high saturated vapor pressure such as zinc (Zn) or strontium (Sr), the particles tend to become polyhedral. On the other hand, even if the powder contains elements with high saturated vapor pressure, if the temperature is appropriately controlled in the high-temperature heating (spraying) process described below, it is possible to form a polyhedral fine step structure on the particle surface while maintaining the spherical particle shape. This is because the saturated vapor pressure of iron (Fe), the main component of ferrite, is different from that of elements other than iron (Fe). In addition, in order to appropriately control the temperature, it is effective to use the endothermic reaction of the binder component contained in the raw material particles (granulated material) subjected to the high-temperature heating (spraying) process.

[0050] Specifically, the raw material particle composition (M Fe , M m) and the relative binder resin amount (B × (M Fe +M m ) / M m It is preferable to adjust the content of M to satisfy the following formula (1). Fe is the number of moles of iron (Fe), M m is the total number of moles of metal elements other than iron (Fe), and B is the amount of binder resin (unit: mass %).

[0051]

number

[0052] If the relative binder resin amount is below 0.06, the amount of binder component added will be too small. The temperature of the thermal spray flame will be too high, making it difficult to form a step structure even in spherical particles. On the other hand, if the relative binder resin amount is above 0.30, the amount of binder component added will be too large. As a result, the temperature of the thermal spray flame will drop too much, and a large amount of irregularly shaped particles will be formed in addition to spherical particles. It is more preferable that the relative binder resin amount is 0.07 or more and 0.20 or less.

[0053] <Thermal spraying> Next, the obtained granules are thermally sprayed to obtain a thermal spray material. In thermal spraying, a mixture of combustion gas and oxygen can be used as the combustible gas combustion flame. The volume ratio of the combustion gas to oxygen is preferably 1:3.5 to 1:6.0, more preferably 1:4.9 to 1:6.0, and particularly preferably 1:4.9 to 1:5.3. This allows the volatilized material to condense, and the formation of particles with a small particle size can be favorably promoted. For example, a combustion gas of 7 Nm 3 / hr for oxygen 35Nm 3 / hour (the volume ratio of combustion gas to oxygen is 1:5).

[0054] Under conditions where there is an excessive amount of combustion gas or oxygen, the gas or oxygen not used in the combustion may take away the heat generated by the combustion, causing the flame temperature to drop. Therefore, it is not preferable to perform thermal spraying under such conditions. The amount of excess combustion gas not used in the combustion is preferably 20% by volume or less of the amount of combustion gas supplied. Also, the amount of excess oxygen not used in the combustion is preferably 20% by volume or less of the amount of oxygen supplied.

[0055] Examples of the combustion gas used in thermal spraying include combustible gases such as propane gas, propylene gas, and acetylene gas, and among these, propane gas is preferred. In order to transport the granulated material into the combustible gas, a carrier gas such as nitrogen, oxygen, or air can be used. The flow rate of the transported granulated material is preferably 20 to 60 m / sec. The thermal spraying temperature is preferably 1000 to 3500°C, and more preferably 2000 to 3500°C. By satisfying these conditions, the volatilized material is condensed, and the formation of particles with a relatively small particle size can be more suitably promoted. In addition, the shape of the obtained ferrite particles can be more suitably adjusted.

[0056] Next, a cooling gas is introduced into the particles ferrite-formed by thermal spraying to rapidly cool and solidify them, and the solidified particles are collected in a cyclone or filter. The collected ferrite particles can then be classified as necessary. Air at room temperature can be used as the cooling gas. Alternatively, air or inert gases (nitrogen gas, helium gas, argon gas, etc.) that are lower in temperature than room temperature can be used to prevent rapid cooling and oxidation. In classification, the particle size is adjusted to the desired particle size using existing techniques such as air classification (airflow classification), mesh filtration, sieve classification, and sedimentation. It is also possible to separate and collect large particles in one process by airflow classification such as a cyclone.

[0057] In order to obtain ferrite particles with a step structure (spherical step particles), it is important to spray the granulated material under specified conditions. The entire granulated material is melted during spraying and then rapidly cooled. Although the detailed mechanism is unknown, it is speculated that a polygonal step structure reflecting the crystal structure of ferrite is formed on the particle surface during high-temperature melting, and this structure is maintained when the granulated material is rapidly cooled. In other words, when the granulated material containing a binder is sprayed, the binder is decomposed and the raw material primary particles are changed into ferrite particles (spherical step particles). The binder decomposition is an endothermic reaction, and even if a step structure is formed, it is difficult to apply more heat than necessary. Therefore, it is speculated that a clear step structure is easily generated and maintained. On the other hand, if the granulated material does not contain a binder or contains very little binder, it receives excessive heat from the flame. Therefore, even if a step structure is formed, the step structure will not be maintained throughout the particle over time and will disappear locally. The binder content of the granulated material is preferably 0.007% by mass or more relative to the mass of the granulated material. On the other hand, if the binder content of the granulated material is excessive, the endothermic reaction becomes too large, and particles that are not perfectly spherical tend to be generated. The binder content of the granulated material is preferably 0.100% by mass or less, more preferably 0.050% by mass or less, based on the mass of the granulated material.

[0058] In addition, when the granulated material is sintered at a temperature below the melting temperature to produce ferrite particles, it is believed that a polygonal step structure is difficult to form, and even if it is formed, the step structure disappears when cooled slowly. For example, in Patent Document 6, a raw material mixture is granulated and then sintered at a temperature below 1000°C to produce a carrier core material having step-like irregularities on the particle surface (Claim 1 of Patent Document 6). However, this step-like irregularity is concentric and has a different shape from the step structure targeted by this embodiment.

[0059] The conditions during thermal spraying are also important. That is, the mechanism of the appearance of the step structure changes depending on the time it takes for the raw material particles to cool down from the temperature when passing through the thermal spray flame (the amount of heat given to the raw material particles) to room temperature. In particular, the step structure appears when the primary raw material particles that have passed through a flame of high temperature are rapidly cooled. Even with the same temperature flame, the step structure becomes less likely to appear if the number of passes per unit time of the primary raw material particles (the amount of processing per hour) increases. Therefore, from the viewpoint of appearing the step structure, it is preferable to supply a small amount of raw material for thermal spraying. For example, the supply amount is preferably 20 kg / hour or less, more preferably 10 kg / hour or less, and most preferably less than 5 kg / hour.

[0060] The combustion gas ratio is preferably 1.05 or more and 2.00 or less. Here, the combustion gas ratio is the amount of combustion gas (Nm m ) used for net combustion relative to the amount of raw material supplied (kg / hour). 3 / time) and can be calculated according to the following formula (2).

[0061]

number

[0062] The amount of combustion gas used for net combustion (Nm 3 / time) can be calculated according to the following formula (3) or (4).

[0063]

number

number

[0064] 3. Ferrite-resin composite material The ferrite resin composite material of the present embodiment includes the above-mentioned ferrite powder and a resin. This composite material suppresses the ferrite particles from falling off without impairing moldability and packing ability.

[0065] Examples of resins constituting the composite material include epoxy resins, urethane resins, acrylic resins, silicone resins, polyamide resins, polyimide resins, polyamideimide resins, fluororesins, and combinations thereof. The silicone resin may be a modified silicone resin modified with acrylic, urethane, epoxy, and / or fluorine.

[0066] The composite material may contain components other than the ferrite powder and the resin, such as, for example, a solvent, a filler (organic filler, inorganic filler), a plasticizer, an antioxidant, a dispersant, a colorant such as a pigment, and / or thermally conductive particles.

[0067] The ratio of the ferrite powder to the total solid content in the composite material is preferably 50 to 95 mass%, more preferably 80 to 95 mass%. The ratio of the resin to the total solid content in the composite material is preferably 5 to 50 mass%, more preferably 5 to 20 mass%. By setting the ratio of the ferrite powder and the resin within the above ranges, the dispersion stability of the ferrite powder in the composite material, as well as the storage stability and moldability of the composite material, become excellent, and the mechanical strength, electromagnetic wave shielding performance, and other properties of the composite (molded product) obtained by molding the composite material become excellent.

[0068] 4. Electromagnetic shielding materials, electronic materials, electronic components The electromagnetic shielding material, electronic material, or electronic part of the present embodiment includes the above-mentioned ferrite resin composite material. The electromagnetic shielding material, electronic material, or electronic part may be produced by molding the composite material by a known method. The molding method is not particularly limited, and examples thereof include compression molding, extrusion molding, injection molding, blow molding, and calendar molding. Alternatively, a coating film of the composite material may be formed on a substrate.

[0069] Thus, the ferrite powder of this embodiment is characterized by including ferrite particles having a specific shape and a specific step structure on the surface. This ferrite powder is suitable for use as an electromagnetic shielding material, electronic material, and / or electronic component. In addition, the ferrite powder, ferrite resin composite material, and electromagnetic shielding material, electronic material, or electronic component of this embodiment can suppress the ferrite particles from falling off without impairing moldability and packing ability. In contrast, Patent Documents 1 to 5 do not describe the surface structure of ferrite particles, and do not address particle falling off as an issue. In addition, the carrier core material disclosed in Patent Document 6 has a concentric step-like unevenness on its surface, which is different in shape from the step structure targeted by this embodiment. In addition, the issue is to improve the charge imparting ability of the carrier core material (

[0026] of Patent Document 6), and is unrelated to particle falling off. EXAMPLES

[0070] This embodiment will be more specifically described by the following examples.

[0071] (1) Preparation of ferrite powder Example 1 <Raw material mixture> The raw material is iron oxide (Fe 2 O 3 ) and trimanganese tetroxide (Mn 3 O 4 ) were used, and iron (Fe) and manganese (Mn) were weighed out so that the molar ratio of iron (Fe) and manganese (Mn) was Fe:Mn=7.8:1, and mixed using a Henschel mixer.

[0072] <Pre-calcination and grinding> The resulting mixture was pre-fired in a rotary kiln. The pre-fired mixture was held in air at 900°C for 4 hours. The pre-fired product was coarsely pulverized using a dry bead mill (3 / 16 inch steel ball beads), and then water was added and the product was finely pulverized using a wet bead mill (0.65 mm zirconia beads). The particle size of the pulverized powder was 2.26 μm.

[0073] <Granulation> To the obtained slurry, polyvinyl alcohol (PVA, 10% aqueous solution) was added as a binder in an amount of 0.017% by mass in terms of solid content, and the slurry to which the binder was added was then granulated using a spray dryer.

[0074] <Thermal spraying> The resulting granules were sprayed in a combustible gas combustion flame and quenched. The spraying was carried out at a propane gas flow rate of 7.0 m 3 / hour, oxygen flow rate 35m 3 The conditions were a heating rate of 4.5 kg / hour and a raw material supply rate of 4.5 kg / hour. Air was introduced into the combustion gas immediately after thermal spraying to rapidly cool the thermal sprayed material, and the rapidly cooled thermal sprayed material was collected in a cyclone installed downstream of the air flow. Coarse powder was removed from the obtained thermal sprayed material using a sieve, and fine powder was further removed using a classification device to obtain ferrite powder consisting of multiple manganese (Mn)-based ferrite particles.

[0075] Example 2 Immediately after spraying, air was introduced into the combustion gas for cooling to rapidly cool the sprayed material, and the rapidly cooled sprayed material was collected in a bag filter installed downstream of the air flow. Although coarse powder was removed from the obtained sprayed material by air flow classification, fine powder was not removed. Ferrite powder was produced in the same manner as in Example 1 except for the above.

[0076] Example 3 When the raw materials were mixed, iron (Fe) and manganese (Mn) were weighed so that the molar ratio of Fe:Mn was 3.0:1. During granulation, 0.044 mass% of polyvinyl alcohol (PVA, 10% aqueous solution) was added as a binder to the slurry in terms of solid content. Otherwise, ferrite powder was produced in the same manner as in Example 1. In Example 3, the particle size of the pulverized powder after calcination and pulverization was 2.52 μm.

[0077] Example 4 Immediately after spraying, air was introduced into the combustion gas for cooling to rapidly cool the sprayed material, and the rapidly cooled sprayed material was collected in a bag filter installed downstream of the air flow. Although coarse powder was removed from the resulting sprayed material by air flow classification, fine powder removal was not performed. Ferrite powder was otherwise produced in the same manner as in Example 3.

[0078] Example 5 When the raw materials were mixed, iron (Fe) and manganese (Mn) were weighed so that the molar ratio of Fe:Mn was 14.0:1. During granulation, 0.010 mass% of polyvinyl alcohol (PVA, 10% aqueous solution) was added as a binder to the slurry in terms of solid content. Otherwise, ferrite powder was produced in the same manner as in Example 1. In Example 5, the particle size of the pulverized powder after calcination and pulverization was 2.01 μm.

[0079] Example 6 Thermal spraying was performed using propane gas at a flow rate of 7.5 m 3 / hour, oxygen flow rate 35m 3 The conditions were: 10 ...

[0080] Example 7 Thermal spraying was performed using propane gas at a flow rate of 7.5 m 3 / hour, oxygen flow rate 37.5m 3 The conditions were a heating rate of 1000 / hour and a raw material supply rate of 6 kg / hour. Air for cooling was introduced into the combustion gas immediately after thermal spraying to rapidly cool the thermal sprayed material, and the rapidly cooled thermal sprayed material was collected in a cyclone installed downstream of the air flow. Ferrite powder was produced in the same manner as in Example 1 except for the above.

[0081] Example 8 Immediately after spraying, air was introduced into the combustion gas for cooling to rapidly cool the sprayed material, and the rapidly cooled sprayed material was collected in a bag filter installed downstream of the air flow. Although coarse powder was removed from the obtained sprayed material by air flow classification, fine powder was not removed. Ferrite powder was produced in the same manner as in Example 7.

[0082] Example 9 (Comparison) Instead of thermal spraying, the granulated material was debindered and sintered, and then the sintered material was crushed and coarse and fine powders were removed from the crushed material by air classification. The debindering and sintering were performed by holding the granulated material in air at 650°C for 4 hours, and then holding it in an atmosphere of 0% oxygen by volume at 1250°C for 4 hours. Crushing was performed using a hammer crusher. Ferrite powder was produced in the same manner as in Example 1 except for the above.

[0083] For Examples 1 to 9, the production conditions of the ferrite powder are shown in Table 1.

[0084] (2) Preparation of composite material Ferrite resin composite materials were prepared using the ferrite powders obtained in Examples 1 to 9. The composite materials were prepared as follows. The obtained ferrite powders and commercially available epoxy resin were weighed out so that the volume of the ferrite powder was 60% by volume, and the mixture was made into a paste using a planetary centrifugal mixer. The viscosity of the paste was measured using a viscometer. The obtained paste was poured into a silicone resin mold and then thermally cured to prepare a sample (composite material) for evaluating detached particles.

[0085] (3) Evaluation The ferrite powders and composite materials obtained in Examples 1 to 9 were evaluated for various properties as follows.

[0086] <Elemental analysis - metal component content> The metal content of the ferrite powder was measured as follows. First, 0.2 g of the sample (ferrite powder) was weighed, and 60 ml of pure water, 20 ml of 1N hydrochloric acid, and 20 ml of 1N nitric acid were added to it, and then heated to prepare an aqueous solution in which the sample was completely dissolved. The obtained aqueous solution was placed in an ICP analyzer (Shimadzu Corporation, ICPS-10001V) and the metal content was measured.

[0087] <Particle surface structure - Ps> The surface structure of particles in the ferrite powder was evaluated as follows. First, the ferrite powder was observed using a scanning electron microscope (SEM; Hitachi High-Technologies Corporation, SU-8020). During observation, the magnification was set to 50,000 times for particles with an average particle size of 2 μm or more, and 200,000 times for particles with an average particle size of less than 2 μm. In either case, the image was taken with 1 to 30 particles, preferably 1 to 10 particles, with a horizontal Feret diameter of 0.3 μm or more in the field of view.

[0088] Ten fields of view were photographed randomly, and the presence or absence of polygonal steps was confirmed for particles with a horizontal Feret diameter of 0.3 μm or more. The proportion of spherical-like step particles (Ps) was calculated according to the following formula (5). Note that particles with a horizontal Feret diameter of less than 0.3 μm may not be able to determine the presence or absence of steps because the electron beam passes through the particle during photography. For this reason, they were excluded from the evaluation.

[0089]

number

[0090] Here, N i is the number of particles with a horizontal Feret diameter of 0.3 μm or more photographed in the i-th field of view, and n i is the number of particles with spherical-like steps among the particles photographed in the i-th field of view. A particle that is partially outside the photographed field of view is also counted as one particle.

[0091] <Particle surface structure - Hs> When observing with a scanning electron microscope (SEM), the magnification was set to 200,000 times, and 1 to 30, preferably 1 to 10, spherical-like step particles were photographed so that they were in the center of the field of view. The average step interval (Hs) was calculated from the scale of the SEM photograph according to the following formula (6).

[0092]

number

[0093] Figure 1 shows an example of an SEM image of a spherical-like stepped particle. The arrow (→) in the image indicates the perpendicular direction to the steps that are arranged in parallel. The numbers (1, 2, 3...) in the image represent each step. Note that the image should be taken so that the steps can be distinguished; it is not necessary for the entire particle to fit into one field of view. When calculating Hs, any one step on a particle can be selected. If there are multiple steps with different directions, it is acceptable to calculate from the step that is roughly representative of the particle. The number of steps should be four or more.

[0094] <Shape factor - average particle size 2μm or more> For particles with an average particle size of 2 μm or more, the shape factors (SF-1 and SF-2) of the ferrite powder were determined using a particle image analyzer (Malvern Panalytical, Morphologi G3). First, the ferrite powder was analyzed using the particle image analyzer. During the analysis, image analysis was performed on each of the 30,000 particles in the powder, and the circularity, perimeter, and circle equivalent diameter (CE diameter) were automatically measured. An objective lens with a magnification of 10x was used for this purpose. The particles were dispersed on a slide glass using a dispersion tool attached to the device. The sample amount was 3 mm. 3 The particles were dispersed under the following conditions: dispersion pressure: 5 bar.

[0095] Among the obtained data, the averages of the data of particles within ±5% of the volume average particle size were taken as the average circularity, average perimeter, and average circle equivalent diameter (CE diameter), and SF-1 and SF-2 were calculated according to the following formulas (7) and (8).

[0096]

number

number

[0097] <Shape factor - average particle size less than 2μm> For particles with an average particle size of less than 2 μm, the shape factors (SF-1 and SF-2) of the ferrite powder were determined using a FE-SEM (field emission scanning electron microscope). First, images of the ferrite powder were taken in multiple fields of view using the FE-SEM. The images were taken at a magnification of 100,000 times. The images were then analyzed using image analysis software (Image-Pro Plus). For the analysis, 100 particles with a circle-equivalent diameter of ±5% of the volume average particle size were selected and analyzed individually. The maximum length (horizontal Feret diameter) R (unit: μm), projected perimeter L (unit: μm) and projected area S (unit: μm 2 ) and the circle equivalent diameter r (unit: μm) were measured.

[0098] Next, SF-1 and SF-2 of each particle were calculated according to the following formula (9) and formula (10), and the respective average values ​​were taken as SF-1 and SF-2 of the ferrite powder.

[0099]

number

number

[0100] <Ratio of irregular particles> The ratio of irregularly shaped particles in the ferrite powder was determined as follows. During analysis using a particle image analyzer, the number N of particles with a circularity of 0.965 or more and 1.000 or less and the number n of particles with a circularity of 0.950 or more and less than 0.965 were counted, and the ratio of irregularly shaped particles was calculated according to the following formula (11). Note that particles with a circularity of less than 0.950 may be aggregated particles. For this reason, such particles were excluded from the evaluation.

[0101]

number

[0102] <Tap density> The tap density of the ferrite powder was measured in accordance with JIS Z 2512-2012 using a USP tap density measuring device (Hosokawa Micron Corporation, Powder Tester PT-X).

[0103] <True specific gravity> The true specific gravity of the ferrite powder was measured in accordance with JIS Z8807:2012 using the gas displacement method. Specifically, the measurement was carried out using a fully automatic true density measuring device (Mountech Co., Ltd., Macpycno).

[0104] <Particle size distribution> The particle size distribution of the ferrite powder was measured as follows. First, 10 g of the sample (ferrite powder) and 80 ml of water were placed in a 100 ml beaker, and 2 drops of sodium hexametaphosphate were added as a dispersant. Then, it was dispersed using an ultrasonic homogenizer (SMT Co., Ltd., UH-150 type). At this time, the output level of the ultrasonic homogenizer was set to 4 and dispersion was carried out for 20 seconds. Then, the bubbles formed on the surface of the beaker were removed, and the obtained dispersion was introduced into a laser diffraction particle size distribution measuring device (Shimadzu Corporation, SALD-7500nano) for measurement. The measurement conditions were a pump speed of 7, an internal ultrasonic irradiation time of 30, and a refractive index of 1.70 - 050i. By this measurement, the 10% diameter (D10), 50% diameter (volume average particle diameter, D50), and 90% diameter (D90) in the volume particle size distribution were determined.

[0105] <BET specific surface area> The BET specific surface area of ​​the ferrite powder was measured using a specific surface area measuring device (Mountec Co., Ltd., Macsorb HM model-1208). First, about 10 g of the ferrite powder was placed on a medicine packing paper and degassed in a vacuum dryer. After confirming that the degree of vacuum was -0.1 MPa or less, the powder was heated at 200°C for 2 hours to remove moisture adhering to the particle surface. Then, the ferrite powder (about 0.5 to 4 g) from which moisture had been removed was placed in a standard sample cell dedicated to the measuring device and accurately weighed with a precision balance. The weighed ferrite particles were then set in the measuring port of the measuring device and measured. The measurement was performed using the one-point method. The measurement atmosphere was set at a temperature of 10 to 30°C and a relative humidity of 20 to 80% (no condensation).

[0106] <Magnetic properties - saturation magnetization, residual magnetization and coercive force> The magnetic properties (saturation magnetization, residual magnetization, and coercivity) of the ferrite powder were measured as follows. First, a sample (ferrite powder) was packed into a cell with an inner diameter of 5 mm and a height of 2 mm, and the cell was set in a vibrating sample magnetic measurement device (Toei Industry Co., Ltd., VSM-C7-10A). A magnetic field was applied and swept up to 5 kOe, and then the applied magnetic field was decreased to draw a hysteresis curve. From the data of this curve, the saturation magnetization σs, residual magnetization σr, and coercivity Hc of the sample were obtained.

[0107] <Magnetic permeability> The magnetic permeability of the ferrite powder was measured using an RF impedance / material analyzer (Agilent Technologies, E4991A) and a magnetic material measurement electrode (16454A). First, 9 g of the sample (ferrite powder) and 1 g of binder resin (Kynar301F: polyvinylidene fluoride) were placed in a polyethylene container (contents 100 ml), and the mixture was stirred and mixed using a ball mill at a rotation speed of 100 rpm. Next, the resulting mixture (about 0.6 g) was filled into a die (inner diameter 4.5 mm, outer diameter 13 mm) and pressed for 1 minute at a pressure of 40 MPa using a press machine to form a molded body. The obtained molded body was heated and cured at 140 °C for 2 hours using a hot air dryer to form a measurement sample. The obtained measurement sample was set in the RF impedance / material analyzer, and the outer diameter, inner diameter, and height of the measurement sample that had been measured in advance were entered. During the measurement, the amplitude was set to 100 mV, and the measurement frequency range was swept from 1 MHz to 3 GHz on a logarithmic scale. The real part (μ') and imaginary part (μ'') of the complex permeability at a frequency of 100 MHz were obtained, and the loss factor (tan δ) was calculated according to the following formula (12).

[0108]

number

[0109] <Ratio of detached particles> The proportion of detached particles from the composite material (composite) was determined as follows. First, the composite material was polished using a polisher to expose the particle cross-section. The polished cross-section was observed in multiple fields of view using a field emission scanning electron microscope (FE-SEM), and the number of ferrite particles and detached particles exposed at the outermost surface was counted. Here, the part where the particles were detached appeared as depressions on the polished cross-section, so the number of depressions was taken as the number of detached particles. The proportion of detached particles was then calculated according to the following formula (13).

[0110]

number

[0111] (4) Results The evaluation results obtained for Examples 1 to 9 are shown in Tables 2 and 3. Furthermore, surface SEM images of the ferrite particles for Examples 1, 4 and 9 are shown in Figs. 1, 2 and 4, respectively.

[0112] As shown in Table 2, the particles contained in the ferrite powders of Examples 1 to 8 produced by thermal spraying were spherical or polyhedral. Among these, Examples 1, 3, 5, and 7, in which the coarse powder was removed by sieve classification and the fine powder was removed by air classification, had a relatively large volume average particle size D50 (3.48 to 3.94 μm) and a spherical particle shape. In contrast, Examples 2, 4, 6, and 8, in which the coarse powder was removed by air classification and the fine powder was not removed, had a relatively small D50 (0.23 to 0.83 μm) and were polyhedral. However, it was found that all of Examples 1 to 8 had a small shape factor SF-1 (101 to 102) and excellent sphericity.

[0113] Examples 1 to 8 had a polygonal step structure on the particle surface. Therefore, when the composite material was formed, the proportion of detached particles was small, at 6% or less by number. In particular, in Examples 1, 3, and 5, in which the proportion (Ps) of spherical-like step particles was high, at 64 to 67%, almost no detached particles were observed.

[0114] In contrast, the ferrite powder of Example 9 produced by sintering contained granular particles, not spherical or polyhedral. Also, Example 9 did not have a step structure on the particle surface. Therefore, when the composite material was produced, the proportion of detached particles was as high as 15% by number.

[0115] [Table 1]

[0116] [Table 2]

[0117] [Table 3]

Claims

1. The present invention includes at least spherical or polyhedral ferrite particles having a step structure on the surface thereof, the step structure has a polygonal contour on the surface of the ferrite particle, The outline of the step structure is configured in a closed linear shape.

2. The ferrite powder according to claim 1 , wherein the step structure has two or more steps.

3. The ferrite powder according to claim 1 or 2, wherein the ferrite powder has a shape factor SF-1 of 100 to 110.

4. The ferrite powder according to any one of claims 1 to 3, wherein the ferrite powder has a 50% diameter (D50) in a volume particle size distribution of 0.10 to 20.00 µm.

5. The ferrite powder has a manganese (Mn) ferrite composition having a manganese (Mn) content of 4.0 to 17.0 mass% and an iron (Fe) content of 50.0 to 70.0 mass%. The ferrite powder according to any one of claims 1 to 4.

6. A ferrite resin composite material comprising the ferrite powder according to any one of claims 1 to 5 and a resin.

7. An electromagnetic wave shielding material, electronic material, or electronic part, comprising the ferrite resin composite material according to claim 6.

Citation Information

Patent Citations

  • Rail clamp apparatus

    JP1984021801A

  • Ferrite-resin composite composition

    JP1992154869A

  • Radio wave absorber material powder and manufacture

    JP1992304700A

  • Spherical sintered ferrite particle and resin composition for semiconductor sealing using the same, and semiconductor unit obtained by using the resin composition

    JP2006160560A

  • Spherical ferrite powder, resin composition containing spherical ferrite powder and molded body using resin composition

    JP2016060682A